INNOVATION IN ISLAMIC RELIGIOUS EDUCATION LEARNING IN ELEMENTARY SCHOOLS: ENHANCING STUDENT CREATIVITY WITH CANVA MEDIA - Ahmad Zubaidi; Hafilatul Hasanah (PGMI Fakultas Tarbiyah Universitas Islam Jember, 2026)
The transformation of digital-based learning in elementary schools is an inevitable requirement in facing the dynamics of 21st-century education, including in the teaching of Islamic Religious Education (PAI). This study aims to explore strategies for utilizing Canva media by teachers to enhance student creativity in PAI learning at Cahaya Cendekia Elementary School. This study uses a qualitative case study approach with data collection techniques in the form of in-depth interviews, classroom observations, and visual documentation. The results show that Canva is effectively utilized by teachers to create visually appealing Student Worksheets (LKPD), thereby stimulating students' attention and participation. Students' creativity develops through non-digital activities such as describing religious illustrations, composing narratives of prophets' stories, coloring, and verbally conveying moral messages. In addition, the use of Canva also had an impact on improving teacher professionalism and strengthening institutional identity through published visual documentation. Although students were not directly involved in using the application due to age and facility limitations, this approach succeeded in creating a contextual, enjoyable learning environment that encouraged the creative expression of religious values. Thus, Canva has become a relevant and transformative visual medium in the development of Islamic Education learning at the elementary school level.